Proposal for optimizing the management of industrial scaffolding materials by the Lean Manufacturing philosophy - Santos, André Luís Kimura; Nascimento, Lucas Bergami; Servare Junior , Marcos Wagner Jesus; Bernardina, Fernanda Pecemilis Dalla (Brazilian Journal of Production Engineering, 2023)
The present study has the purpose of applying some tools of the Lean Manufacturing philosophy to contribute positively in the management of industrial scaffolding material of a company that provides industrial maintenance service. According to the surveys of material movements within the first half of 2022 and brainstorming, carried out with the operational manager and operational supervisor, it was possible to apply the ABC Curve, 5W2H and FMEA that not only classified the importance of each item, but also, proposed action plans for the problems that caused waste of physical and digital resources. Therefore, the data collected and the optimization proposals will serve for more assertive decision-making that will consequently increase the company’s profitability.